URABAYEN, Julia y LEÓN-CASERO, Jorge (Eds.) (2019): Disciplines of the City. New Forms of Governance in Today´'s Postmetropolises, New York: Nova Science Publishers.: New Forms of Governance in Today´´ s Postmetropolises - Ríos Ramírez, Alejandra (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: URABAYEN, Julia y LEÓN-CASERO, Jorge (Eds.) (2019): Disciplines of the City. New Forms of Governance in Today´'s Postmetropolises, New York: Nova Science Publishers.